Resampling methods in survey sampling - Krapavickaitė, Danutė; Šalučkienė, Genovaitė (Lietuvos matematikos rinkinys, 2000)
Aim of this paper is to estimate variances of the estimates of the population totals using resampling methods and to compare them with the known variances of the estimates.